Relative Conservation Status of Bird Orders With Special Attention to Raptors - McClure, Christopher J. W.; Rolek, Brian W. (Frontiers in Ecology and Evolution, 2020)
Birds, especially raptors, play important roles in ecosystems. We examine the International Union for the Conservation of Nature’s (IUCN) Red List to determine which orders of birds have proportionally more or fewer species listed as threatened or declining compared to the Class-wide average. We further examine whether raptors are more threatened or declining than non-raptors and whether the order Accipitriformes is particularly threatened even when excluding Old World vultures—which are especially imperiled. Our results reveal heterogeneity across bird orders in proportions of threatened and declining species, with some orders having greater or lower proportions than the Class-wide proportion. We also show that the proportions of threatened species in each order are correlated with the proportion of declining species. Raptors have both greater proportions of threatened and declining species than non-raptors and Accipitriformes has greater-than-average proportions of threatened and declining species, even if Old World vultures are removed from the analysis. Our results should serve as a framework for discussion of the relative conservation status of bird orders, especially raptors, which are in need of increased conservation attention.